A summertime mystery - Blyton, Enid (A wishing-chair adventure, 2020)
A magical wishing-chair short story from Enid Byton with brand new full-colour illustrations! Mollie and Peter are the luckiest children in the world - they have a very special flying chair to take them wherever they wish! Join Mollie and Peter on a perilous trip to a disappearing island and meet a mysterious wizard carried on the wind...